2004
DOI: 10.1111/j.0435-3684.2004.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Monuments, memory and marginalisation in adelaide's prince henry gardens

Abstract: Social and cultural dominance is (re)produced in the landscape by the exclusion or marginalisation of subordinate and minority groups. This paper illustrates the long-standing and ongoing exclusion of representations of indigeneity in and around Prince Henry Gardens, part of one of the most significant cultural and memorial sites in South Australia. Prince Henry Gardens is home to a large number of monuments and memorials that commemorate almost solely non-indigenous people and events. This is a selective and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 30 publications
0
16
0
4
Order By: Relevance
“…In these narratives, white explorers and colonizers are cast as civilized heroes while natives are depicted as primitive and inferior, if they are shown to exist at all. The monuments found in Adelaide's Prince Henry Gardens-one of South Australia's most important symbolic sites-show clear evidence of this type of symbolic marginalization (Hay et al 2004). All of the statues, busts, and memorials that geographers have examined honor people of European, immigrant origin.…”
Section: Approaches To Studying Memorial Landscapesmentioning
confidence: 99%
“…In these narratives, white explorers and colonizers are cast as civilized heroes while natives are depicted as primitive and inferior, if they are shown to exist at all. The monuments found in Adelaide's Prince Henry Gardens-one of South Australia's most important symbolic sites-show clear evidence of this type of symbolic marginalization (Hay et al 2004). All of the statues, busts, and memorials that geographers have examined honor people of European, immigrant origin.…”
Section: Approaches To Studying Memorial Landscapesmentioning
confidence: 99%
“…In contrast, the colonising culture's ‘originary stories’ are to be found in the constructed landscape; the monuments, the memorials and the churches. North Terrace, Adelaide's premier cultural boulevard with its numerous cultural institutions, statues and memorials (Hay et al , 2004) is a case in point.…”
Section: The Evolution Of Other Forms Of Indigenous Expression and Comentioning
confidence: 99%
“…Public space, as a space of both contestation and reconciliation, can be seen to reflect not only the more recent reconciliation process but also the evolution of the recognition and social inclusion of Indigenous people in Australia. A number of cultural geographers (Hansford, 1996; Jacobs, 1996; Dunn, 1997; Osborne, 2001; Hay et al , 2004) have drawn attention to the ways in which public space representations of cultural history help shape personal and civic identity and a sense of belonging or, conversely, of not belonging. They also suggest that a change in public representations can potentially help to reshape social understandings and cultural identities.…”
Section: Introductionmentioning
confidence: 99%
“…A similar movement has taken place in New Zealand with the reinstatement of Maori toponyms as a way of redressing that group's historical marginalization, although that process, as in Australia, has evoked resistance and accusations of reverse racism from conservative whites (Berg and Kearns 1996). As Hay et al (2004) found, the racial politics of public commemoration and renaming places can also be characterized by locational debates and discrimination even as authorities seek to bring greater public attention to the representation of indigenous histories. In Adelaide, Australia, for example, city and state sponsored efforts to recognize Aborigines through place renaming 'overwhelmingly link indigeneity with the city's periphery, not its cultural core' and 'the landscape of indigenous (historical) presence is confined to large parkland areas' that are perceived by many people as dangerous and forbidding (Hay et al 2004: 210).…”
Section: Introductionmentioning
confidence: 97%